2022
DOI: 10.1039/d2tc00850e
|View full text |Cite
|
Sign up to set email alerts
|

High-performance ultra-narrow-band green-emitting phosphor LaMgAl11O19:Mn2+ for wide color-gamut WLED backlight displays

Abstract: Explorations of narrow-band green-emitting phosphors have attracted much attention due to their great application potentials in wide color-gamut wLEDs backlight display. Herein, a high-performance narrow-band green-emitting phosphor LaMg0.72Al11O19:0.28Mn2+ (LMAO:0.28Mn2+) was...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 35 publications
0
25
0
3
Order By: Relevance
“…Due to particular biological activity, crown ether’s derivate and N -containing heterocyclic chemicals and their derivatives have been widely employed in agronomy and medicine [ 18 ]. Similar organic chemicals are of interest in pharmacology as effective tissue oxygenators and antidepressants, as well as in biotechnology; these compounds are employed for macromolecule binding [ 19 , 20 , 21 , 22 , 23 ]. N -containing heterocyclic compounds and macrocycle derivative crown ethers have remarkable photochemical, catalytic, and luminescent capabilities, indicating that they might be used to diagnose and cure various ailments.…”
Section: Introductionmentioning
confidence: 99%
“…Due to particular biological activity, crown ether’s derivate and N -containing heterocyclic chemicals and their derivatives have been widely employed in agronomy and medicine [ 18 ]. Similar organic chemicals are of interest in pharmacology as effective tissue oxygenators and antidepressants, as well as in biotechnology; these compounds are employed for macromolecule binding [ 19 , 20 , 21 , 22 , 23 ]. N -containing heterocyclic compounds and macrocycle derivative crown ethers have remarkable photochemical, catalytic, and luminescent capabilities, indicating that they might be used to diagnose and cure various ailments.…”
Section: Introductionmentioning
confidence: 99%
“…Single-particle PL is another effective tool for the characterization of the charge transfer process in plasmonic photocatalysis . In principle, the recombination of hot carriers generated from interband and intraband transitions will lead to PL emissions. The changes in PL intensity thus can be used to monitor the charge transfer process. Lou et al observed a reduced dipole LSPR PL (at ∼1.8 eV) intensity of Au triangular nanoprisms after Pt surface modification (Figure e) .…”
Section: Preparation and Characterization Of Active Site-engineered P...mentioning
confidence: 99%
“…Presently, the research on narrow-band green emitters for backlight display mainly includes quantum dots, Mn 2+ activated phosphors, and Eu 2+ activated phosphors . Due to the disadvantages of toxicity, poor thermal stability, and high price, quantum dots currently cannot be commercialized on a large scale. The long decay time of the Mn 2+ -activated narrow-band green phosphors results in a trailing ghost signal, which limits its commercial application. , Moreover, the disadvantages of instability and difficult synthesis exist in sulfide phosphors and nitride phosphors, respectively. , As a result, Eu 2+ -activated oxide phosphors have great advantages in the research of narrow-band green phosphors because of their short decay time, easy synthesis, relative stabilization, and low cost. Therefore, there is an urgent need to explore Eu 2+ -doped narrow-band green oxide phosphors capable of realizing a wide color gamut.…”
Section: Introductionmentioning
confidence: 99%